Tax crimes in Italy using accounting documents - Cieśla, Rafał; Pavone, Pietro; Grębowiec-Baffoni, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Contemporary document research involves the need to use the latest technologies and analytical techniques that provide the most complete possible knowledge of contemporary issues and methods of document research. Documents are used to record legal actions and events of legal significance. By their essence, they are therefore closely related to the sphere of rights and obligations of a specific person or institution. Crimes against documents pose a threat to the proper functioning of the state and thus the development of every enterprise. They affect, directly or indirectly, the misallocation of financial resources at the disposal of an enterprise. Forging documents may be aimed at obtaining unauthorized access to specific sources of financing, influencing key management decisions made in the company, or, finally, concealing inconvenient facts. On the other hand, the social harm suffered as a result of forging documents of evidence significance in tax matters may be enormous. For this reason, it is necessary to deepen the knowledge of the dynamics characterizing document forgery in the sphere of economic activity in order for the state to activate mechanisms able to prevent this type of crime. The article describes the issues of selected tax frauds in Italy with the use of accounting documents.
Keywords: fałszowanie dokumentów; oszustwo podatkowe; przestępstwa podatkowe; kryminalistyka; badanie zakwestionowanych dokumentów